Gender based taxation and the division of family chores - Alberto Alesina; Andrea Ichino; Loukas Karabarbounis (Institute for the Study of Labor (IZA), 2007)
Gender Based Taxation (GBT) satisfies Ramsey's optimal criterion by taxing less the more elastic labor supply of (married) women. This holds when different elasticities between men and women are taken as exogenous and primitive. But in this paper we also explore differences in gender elasticities which emerge endogenously in a model in which spouses bargain over the allocation of home duties. GBT changes spouses' implicit bargaining power and induces a more balanced allocation of house work and working opportunities between males and females. Because of decreasing returns to specialization in home and market work, social welfare improves by taxing conditional on gender. When income sharing within the family is substantial, both spouses may gain from GBT.
Keywords: D13; 330; Optimal taxation; economics of gender; family economics; elasticity of labor supply; Frauenerwerbstätigkeit; Einkommensteuer; Optimale Besteuerung; Arbeitsangebot; Elastizität; Hausarbeit; Wohlfahrtseffekt; Theorie